Level of knowledge on HIV I AIDS among senior high school students - I Nyoman Budi Hartawan; Ketut Dewi Kumara Wati (Paediatrica Indonesiana, 2008)
Background Young people are now the epicenter and bear adisproportionate burden ofHIV/AIDS pandemic. Until now,one of the strategies which are implemented by the govern-ment is by increasing the level of HIV/AIDS knowledge inorder to avoid its spreading.Objective This study was to explore the level of HIV/AIDSknowledge of senior high school's students towards HIV I AIDSat subdistrict ofPetang. The secondary outcome is to comparethe levels of knowledge toward HIV I AIDS between Petang andPelaga Senior high school, between class and gender.Methods This was a descriptive study, conducted between1st to 28th February 2007 in Petang and Pelaga Senior HighSchool. The study subjects are 529 students (all of senior highschool students in subdistrict of Petang, Badung Regency).Data was taken using UNICEF questionnaire 2000 for youngpeople, which had been passed the reliability test with thekappa value of 0.85.Results Most subjects (90.5%) have excellent and goodknowledge and only 9,5% have sufficient knowledge. Level ofknowledge in girls is better than boys with significant differ-ence between them (P=O.OOO), while school and grade didn'tshow any differences (P=0.760) and (P=0.489).Conclusion The level of knowledge of senior High School inSubdistrict ofPetang, Badung Regency toward HIV /AIDS is atexcellent or good level